Pengembangan Sistem Informasi Pemasaran Rumah Berbasis Web - Tuti Meri Anggini (ADA Research Center, 2025)
Marketing is currently a key issue for a company, including PT. Raharja Artha Property. Marketing and employee work, such as sharing information about home marketing and recording consumer reports, is still done manually using Microsoft Excel, which significantly slows down the process. Therefore, a home marketing information system using a website was designed and built to simplify and accelerate the performance of PT. Raharja Artha Property employees in conducting marketing and recording report data more effectively and efficiently. With the successful implementation of the system, employees no longer have difficulty in marketing and recording marketing report data. Performance also becomes easier and faster.